Cost-effectiveness of structured group psychoeducation versus unstructured group support for bipolar disorder: results from a multi-centre pragmatic randomised controlled trial - Camacho, E.M.; Ntais, D.; Jones, S.; Riste, Lisa; Morriss, Richard K.; Lobban, Fiona; Davies, L.M. (Elsevier, 2017)
Background Bipolar disorder (BD) costs the English economy an estimated £5.2billion/year, largely through incomplete recovery. This analysis estimated the cost-effectiveness of group psychoeducation (PEd), versus group peer support (PS), for treating BD. Methods A 96-week pragmatic randomised controlled trial (RCT), conducted in NHS primary care. The primary analysis compared PEd with PS, using multiple imputed datasets for missing values. An economic model was used to compare PEd with treatment as usual (TAU). The perspective was Health and Personal Social Services. Results Participants receiving PEd (n=153) used more (costly) health-related resources than PS (n=151) (net cost per person £1098 (95% CI, £252-£1943)), with a quality-adjusted life year (QALY) gain of 0.023 (95% CI, 0.001-0.056). The cost per QALY gained was £47,739. PEd may be cost-effective (versus PS) if decision makers are willing to pay at least £37,500 per QALY gained. PEd costs £10,765 more than PS to avoid one relapse. The economic model indicates that PEd may be cost-effective versus TAU if it reduces the probability of relapse (by 15%) or reduces the probability of and increases time to relapse (by 10%). Limitations Participants were generally inconsistent in attending treatment sessions and low numbers had complete cost/QALY data. Factors contributing to pervasive uncertainty of the results are discussed. Conclusions This is the first economic evaluation of PEd versus PS in a pragmatic trial. PEd is associated with a modest improvement in health status and higher costs than PS. There is a high level of uncertainty in the data and results.